Circumscription of Abarema (Leguminosae, Caesalpinioideae, Mimosoid clade) - Guerra, Ethiéne; Batista Soares, Marcos Vinicius; Pires Morim, Marli; Vieira Iganci, João Ricardo (Phytotaxa, 2023)
The genus Abarema (Caesalpinioideae, Mimosoid clade), as traditionally circumscribed, emerged as polyphyletic in recent phylogenetic studies. The type species of the genus, Abarema cochliacarpos, is positioned within the Inga clade, separate from the remaining species previously included in the genus (now combined to Punjuba and Jupunba genera). Here we present the new circumscription of Abarema. The two species included in the genus occur in the Atlantic Forest and Caatinga biomes in Brazil. We provide a morphological description of Abarema and its two species, an identification key, conservation status and a geographic distribution map.